A theoretical study on excited-state dynamical properties and laser cooling of zinc monohydride including spin-orbit couplings - Li, Donghui; Fayyaz, Faiza; Bian, Wensheng (Frontiers in Chemistry, 2024)
By means of highly accurate ab initio and dynamical calculations, we identify a suitable laser cooling candidate that contains a transition metal element, namely zinc monohydride (ZnH). The internally contracted multireference configuration interaction method is employed to compute the five lowest-lying Λ-S states of ZnH with the spin-orbit coupling effects included, and very good agreement is obtained between our calculated and experimental spectroscopic data. Our findings show that the position of crossing point of the A 2 Π and B 2 Σ + states of ZnH is above the v′ = 2 vibrational level of the A 2 Π state indicating that the crossings with higher electronic states will have no effect on laser cooling. Hence, we construct a feasible laser-cooling scheme for ZnH using five lasers based on the A 2 Π1/2 → X 2 Σ + 1/2 transition, which features a large vibrational branching ratio R00 (0.8458), a large number of scattered photons (9.8×10 3 ) and an extremely short radiative lifetime (64 ns). The present work demonstrates the importance of electronic state crossings and spin-orbit couplings in the study of molecular laser cooling.